The Values of Islamic Guidance and Counseling in the Novel Hujan by Tere Liye - Vanny Ulan Saqia; Mira Fauziah; M. Yusuf MY (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study aims to analyze the values of Islamic Guidance and Counseling in Tere Liye’s novel Hujan and their relevance to Islamic counseling practice. This study uses a qualitative approach with content analysis. Data were obtained through an in-depth reading of the narrative, dialogues, inner conflicts, and character development of the main character, Lail. The results show that Hujan contains six main values: patience, tawakkal, sincerity, emotional regulation, empathy and social support, as well as motivation and hope for life. These values emerge through Lail’s experiences in facing loss, trauma, psychological pressure, and the process of self-recovery after a disaster. The findings indicate that individual recovery is shaped not only by personal strength, but also by spiritual awareness and supportive social relationships. Hujan can be understood as a reflective medium that bridges psychological and spiritual dimensions. This study concludes that literary works can be used as an alternative medium in Islamic Guidance and Counseling services, particularly through a narrative approach, especially for adolescent counselees who need concrete examples in understanding life experiences, managing emotions, accepting reality, and rebuilding hope in a more religiously meaningful way.